Desafios do direito no século XXI: Diálogos Luso-Brasileiros (Governação e Covid-19) - Fonseca, Isabel Celeste M. (2021)
COMISSÃO CIENTÍFICA Isabel Celeste M. Fonseca Vera Lúcia Viegas Liquidato COORDENAÇÃO EXECUTIVA João Vilas Boas Pinto Larissa Coelho AUTORES Alexandre Cunha Filho / Alexandre G. N. Liquidato / Ana Cláudia Ruy Cardia Atchabahian/ Ana Rita Carneiro / Carmen Silvia Lima de Arruda / Fernanda Calixto / Isabel Celeste M. Fonseca/ João Vilas Boas Pinto / Joel A. Alves / Lilian Regina Gabriel Moreira Pires / Luís Renato Vedovato / Paulo Borba Casella / Vera Lúcia Viegas Liquidato